2007
DOI: 10.1007/s00425-007-0584-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of UDP-glucose: anthocyanin 3′,5′-O-glucosyltransferase from Clitoria ternatea

Abstract: A UDP-glucose: anthocyanin 3',5'-O-glucosyltransferase (UA3'5'GT) (EC 2.4.1.-) was purified from the petals of Clitoria ternatea L. (Phaseoleae), which accumulate polyacylated anthocyanins named ternatins. In the biosynthesis of ternatins, delphinidin 3-O-(6''-O-malonyl)-beta-glucoside (1) is first converted to delphinidin 3-O-(6''-O-malonyl)-beta-glucoside-3'-O-beta-glucoside (2). Then 2 is converted to ternatin C5 (3), which is delphinidin 3-O-(6''-O-malonyl)-beta-glucoside-3',5'-di-O-beta-glucoside. UA3'5'G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
3
19
0
Order By: Relevance
“…The addition of CuSO 4 , FeSO 4 , or ZnSO 4 to 0.5 mM concentration led to the complete loss of UGT90A7 and UGT95A1 activities, while UGT72B11 activity was only reduced to 12, 13, and 89%, respectively. Many Xavonoid glucosyltransferases are inhibited by Zn 2+ , while some anthocyanidin-O-glucosyltransferases are known to keep up moderate activity in the presence of even 1 mM Zn 2+ (Kamsteeg et al 1978;Yabuya et al 2002;Fukuchi-Mizutani et al 2003;Kogawa et al 2007). CoSO 4 at 0.5 mM almost completely inhibited UGT95A1, whereas UGT72B11 and UGT90A7 exhibited commensurable activities (38 and 45%) at the same concentration.…”
Section: Previous Assays Employing Native Enzyme Extracts Frommentioning
confidence: 98%
“…The addition of CuSO 4 , FeSO 4 , or ZnSO 4 to 0.5 mM concentration led to the complete loss of UGT90A7 and UGT95A1 activities, while UGT72B11 activity was only reduced to 12, 13, and 89%, respectively. Many Xavonoid glucosyltransferases are inhibited by Zn 2+ , while some anthocyanidin-O-glucosyltransferases are known to keep up moderate activity in the presence of even 1 mM Zn 2+ (Kamsteeg et al 1978;Yabuya et al 2002;Fukuchi-Mizutani et al 2003;Kogawa et al 2007). CoSO 4 at 0.5 mM almost completely inhibited UGT95A1, whereas UGT72B11 and UGT90A7 exhibited commensurable activities (38 and 45%) at the same concentration.…”
Section: Previous Assays Employing Native Enzyme Extracts Frommentioning
confidence: 98%
“…Studies on ternatin biosynthesis in C. ternatea revealed that delphinidin is not directly glucosylated at the 3 0 -or 5 0 -hydroxyl group, but that glucosylation of delphinidin occurs only when it has a 6 00 -Omalonyl--glucoside at the 3-position. Thus, glucosylation of delphinidin at the 3-hydroxyl group was proposed to be the first key step of ternatin biosynthesis (Kogawa et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies seem to support regiospecificity as a key parameter for UGT substrate specificity. At the same time it is also evident that the presence of a specific structural domain will not by itself assure activity, but should be considered in conjunction with the overall structure of the aglycone (Richman et al, 2005;He et al, 2006;Kogawa et al, 2007;Modolo et al, 2007). Several studies of biochemically described UGTs show some conservation of regiospecificity within phylogenetic groups (Vogt and Jones, 2000;Lim et al, 2003a;Morita et al, 2005;Yonekura-Sakakibara et al, 2007;Caputi et al, 2008).…”
mentioning
confidence: 99%